Elderly women living alone in Spain: the importance of having children. - Reher, David; Requena, Miguel (European Journal of Ageing, 2017)
Our goal in this paper is to analyse the extent to which completed fertility, and in particular childlessness, is a valid predictor of living alone at advanced ages, an increasingly important residential option in advanced societies with crucial implications for social policy design and the organization of welfare services. Based on micro-data from the 2011 Spanish population census, logistic regression techniques are used to assess the impact of fertility on living alone among elderly women net the effect of age, marital status, educational attainment, and other standard population controls. Our results show a clear relationship between completed fertility and living alone. Childlessness is strongly associated with living alone, while having offspring acts as a powerful buffer against living alone, particularly in larger families. A relevant conclusion of this study is that a growing deficit of family resources available for the elderly women will take place in those societies where low fertility and high rates of childlessness have prevailed in recent decades, leading to substantial growth in the number of childless elderly women and in the incidence of living alone during later life.